2001
DOI: 10.1097/00002341-200111000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Mersilene Mesh as an Alternative to Autogenous Fascia Lata in Brow Suspension

Abstract: Mersilene mesh has advantages over other materials for use as a suspensory material in brow suspension surgery, and is associated with a good outcome and low complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
2
22
0
1
Order By: Relevance
“…Mutlu et al 15 reported a rate of 6.3% for granuloma formation. Kemp and MacAndie 16 reported only a single case with extrusion of mesh because of infection. These authors otherwise found a long-term acceptable level of lid position with this material.…”
Section: Discussionmentioning
confidence: 99%
“…Mutlu et al 15 reported a rate of 6.3% for granuloma formation. Kemp and MacAndie 16 reported only a single case with extrusion of mesh because of infection. These authors otherwise found a long-term acceptable level of lid position with this material.…”
Section: Discussionmentioning
confidence: 99%
“…It is also preferred when AFL is not available as in very young children with short legs. 4 15 16 The use of Mersilene mesh as an alternative material in frontalis suspension surgery was described by Downes and Collin in 1989 5 and others [6][7][8][9][10][11][12][13][14] have discussed its use. Mersilene is a sterile wrapped polyester fibre.…”
mentioning
confidence: 99%
“…It has good tensile strength and forms a permanent scaffold for fibrovascular tissue ingrowth, and hence good long term functional results. [5][6][7][8][9][10][11][12][13][14] Materials for frontalis suspension should have good long term results with a low complication rate. Human sclera, banked fascia lata, expanded poly(tetrafluoroethylene) (ePTFE or Gore-Tex), braided polyester, monofilaments, and silicone rod have also been used.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Some centres also recommend the mesh be soaked in antibiotics prior to insertion, but this is not regarded as mandatory.…”
Section: Commentmentioning
confidence: 99%
“…1 The ends of the mesh are secured by a suture or knot, which must be well buried in the forehead. [2][3][4][5][6][7][8][9] The complication rate from extrusion, granuloma, and/or infection ranges from 0 to 35%. [2][3][4][5][6][7][8][9] We report three cases ( Figure 1) referred to an oculoplastic service for management of chronic extrusion and infection of the Mersilene s mesh, where the mesh was excessively bulky and/or the soft tissue thin.…”
mentioning
confidence: 99%